Design and fabrication of the tilting-pad thrust bearing surface profile. Issue 8 (28th August 2018) - Wang, Zhanchao; Guo, Fei; Liu, Ying; Liu, Xiangfeng; Wang, Yuming
Abstract : Purpose: This paper aims to design a new surface profile with simpler processing technology, which makes the bearing load carrying capacity (LCC) close to that of conventional tilting-pad thrust bearing. Design/methodology/approach: The paper analyzes the LCC of the thrust pad with crown profile and designs a new profile, whose performance is similar to the crown profile. The laser method is introduced to fabricate the new profile. The profile with tiny crown height can be fabricated by the laser with the proper parameters. Findings: It was found that there is an optimum value, which is best in terms of the capacity of tilting-pad thrust bearing reach. The new profile with proper parameters can replace the crown profile. Originality/value: The new profile can replace the crown profile and is easier to be made. The new design method could be adopted for designing the pad surface profile of the tilting-pad thrust bearing.